Legal Review of Land Ownership Disputes in the Construction of the Nipa-Nipa Reservoir - Nurul Inayah Yusuf; Andi Suriyaman M. Pide; Andi Tenri Famauri (IHSA Institute, 2022)
This study aims to find out and analyze the causes of overlapping of some of the land owned by PT HK with the heirs and to know and analyze the legal protection of the heirs against the payment of compensation for land whose ownership is still disputed. This research uses the type of empirical legal research, in the form of legal research that functions to see the law in a real sense and examines how the law works in society. The results of this study indicate that the overlapping of some of the land owned by PT HK with the heirs is caused by a number of things, including the non-applicability of the Delimitation Contradictory principle when measuring the object of the dispute, then when a sale and purchase occurs, neither the MS nor PT HK heirs ever down to the location of the object of dispute but only buying and selling of documents related to the location of the object of dispute, and that there is no physical control by PT HK of the object of dispute and proof of ownership shown by both RM heirs and MS heirs is proof of rights long term and legal protection for recipients of compensation is an important matter in land acquisition for development in the public interest because compensation that is fair and in accordance with the rules for land acquisition for development in the public interest which has been well regulated and is clear is a benchmark regarding the level of success of the process. procurement of land for the ban use for public interest. Compensation must be given to the rightful party, in the event that the land object is in a case of ownership, compensation must be deposited at the local court (consignment) and can only be given after a court decision with permanent legal force or a deed of reconciliation.